EUFEMISME DAN DISFEMISME DALAM NOVEL “KORUPSI” KARYA PRAMOEDYA ANANTA TOER - Vioni Saputri; Syahrul Ramadhan; Yasnur Asri (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
Eufimism and Disphemism in "Corruption" Novel by Pramoedya Ananta Toer.The purpose of this study is to explain the form and function of the use of euphemism and disfemism in the novel "Corruption" by Pramoedya Ananta Toer. This type of research includes descriptive research. The data collection technique used is the note-reading technique. Data analysis used agih and equivalent methods. The validity of the data is obtained through intrarater and interrater. The results of this study are classifications of euphemism and disfemism. The classification is classified into words, phrases and sentences. In addition, the background to the use of euphemism and disfemism is the form in the novel "Corruption" in this study.